Efectos de la sentencia previstos en la ley de protección frente a la violencia familiar - Vargas Justiniano, Carlos Javier (2010)
The present investigation addresses the problematic that revolves around family violence, which is very important in our reality because it has current connotations such as the non-application of the effects of the sentence provided for in the law of protection against violence Family as: are the measures of protection; the treatment; The reparation of the damage and the maintenance pension in a mandatory and concomitant way in their sentences. In the development of the present investigation were used data collection methods and techniques such as: dogmatic method, comparative method, method of analysis - synthesis among others. Likewise, the techniques used as the interview, the survey and the signing were appropriate for the development of the subject under study. The first chapter covers all the general aspects of family violence (definition, classification of violence, types of abuse, protection mechanisms, etc.); The second chapter deals with the stages of the investigation process of family violence, the third chapter deals with the reparation of damages in both National Legislation and Comparative Law, in the fourth chapter we touch on the case study. The results have been expressed in tables and statistical graphs, which will allow us a more didactic explanation of the discussion of results. The conclusions and recommendations cover the objectives of the research developed in such a way as to be relevant and applicable to the existing reality in the field of law